PERAN LEMBAGA AMIL ZAKAT YATIM MANDIRI DALAM PENINGKATAN JUMLAH MUZZAKI DI Kantor Cabang YATIM MANDIRI SIDOARJO - Jajang Ahmad Nasrulloh; Ali Hamdan (ICO EDUSHA, 2020)
Zakat is important for Muslims in their worship. Zakat is the third pillar of Islam which is obligatory for every Muslim who is able to help their brother who is entitled to receive it. Zakat is the obligation of every Muslim who is able to pay to those who are more in need. In essence, Allah gives wealth to every Muslim in his portion. However, with the existence of zakat, it will equalize the existing assets of religious communities. This research is a qualitative descriptive research. The data were obtained from the Head of the Yatim Mandiri Sidoarjo Branch. The secondary data is the reference Yatim Mandiri Magazine which will complement the existing documentation. The data collection methods that the writer uses are interviews and observations. The results of this study show that the performance of the Sidoarjo branch of Yatim Mandiri to date is in accordance with the legislation, namely Law No. 23 of 2011 because no party has given a warning for the activities carried out by the Sidoarjo branch of Yatim Mandiri. In carrying out its main duties, the Sidoarjo Branch of Yatim Mandiri is in accordance with the Decree of the Minister of Religion No. 185 of 2016, namely carrying out bookkeeping and administering the acquired assets of zakat and other assets in accordance with applicable regulations, conducting regular internal inspections and if deemed necessary, auditing by a public accountant, publishing audited annual reports through the mass media and submitting annual reports of results implementation of zakat management duties to the Minister of Religion. Keywords : Law No.23 of 2011, Zakat, Muzzaki.